Divergent effects on macrophage biomarkers soluble CD163 and CD206 in axial spondyloarthritis. (18th August 2018) - Heftdal, Line Dam; Loft, Anne Gitte; Hendricks, Oliver; Ashouri Christiansen, Alice; Schiøttz-Christensen, Berit; Arnbak, Bodil; Jurik, Anne Grethe; Østgård, René; Winding Deleuran, Bent; Møller, Holger Jon; Greisen, Stinne Ravn
Abstract: The chronic joint inflammation in axial spondyloarthritis (axSpA) is characterized by infiltration of activated macrophages. The haptoglobin–hemoglobin receptor CD163 and the mannose receptor CD206 are strongly expressed on M2c and M2a macrophages, respectively. We measured the soluble forms of the receptors (sCD163 and sCD206) in plasma (PL) in two axSpA cohorts. All patients fulfil the 2009 Assessment of SpondyloArthritis International Society (ASAS) classification criteria for axSpA and/or the 1984 modified New York criteria for ankylosing spondylitis. The first cohort included anti-TNF-α treated patients with active axSpA ( n =  30); the second cohort included patients in early disease stages ( n =  38). Plasma sCD163 and sCD206 were both within the reference interval of healthy controls (HC), but sCD163 decreased slightly during anti-TNF-α treatment [baseline: 1.49 mg/L (IQR: 1.22–1.77 mg/L, 12 weeks: 1.29 (IQR: 1.09–1.57) mg/L, 20 weeks: 1.25 (IQR: 0.99–1.75) mg/L, 52 weeks: 1.39 (IQR: 1.15–1.78) mg/L], while sCD206 increased [baseline: 0.17 (IQR: 0.13–0.21) mg/L, 12 weeks: 0.19 (0.16–0.23) mg/L, 20 weeks: 0.20 (0.14–0.24) mg/L, 52: 0.19 (IQR: 0.14–0.23) mg/L], pointing toward a shift in polarization of involved macrophages. Plasma levels of sCD206 proved significantly higher in patients with early disease stages and definite radiological sacroiliitis ( n =  10). This was not the case for sCD163. A significant increase in response to anti-TNF-α treatment, could suggest sCD206 as a marker of response to anti-TNF-α treatment, however, the potential for the two macrophage markers as diagnostic and prognostic indicators of disease in axSpA is weak.